STEM-based approaches to soft skills development: a synthesis of meta-analytic findings and empirical evidence - Rizakhojayeva, Gulnara; Ramankulov, Sherzod; Akeshova, Madina; Nurizinova, Makpal; Tuyakov, Yessenkeldy; Abdrakhmanov, Rustam (Frontiers in Education, 2025)
In today’s modern education system, it is not only professional knowledge and technical skills that are of importance, but also the development of universal competencies known as soft skills—such as communication, collaboration, critical thinking, creativity, and emotional intelligence. The STEM (Science, Technology, Engineering, and Mathematics) education model not only enhances learners’ research capabilities but also provides ample opportunities to foster their soft skills. Accordingly, there is a growing need to systematically analyze effective strategies for developing these skills within STEM learning environments. The aim of this study is to assess the characteristics of soft skills development in STEM education settings through a meta-analysis approach. Based on research conducted across various educational levels, the study seeks to identify key factors influencing the development of these skills and scientifically justify the relationship between soft skills and STEM components. This study includes a systematic review of international and domestic scientific articles, empirical studies, and intervention projects published between 2015 and 2025. The meta-analysis was conducted in accordance with the PRISMA methodology. Review criteria included the types of soft skills and their connection to STEM methodologies. For statistical processing, the software Comprehensive Meta-Analysis 4.0 was utilized. The effectiveness of developing soft skills in STEM education was demonstrated through meta-analysis and empirical research. The meta-analysis revealed that STEM-based interventions have a positive impact on the development of soft skills (Hedges’ g = 0.813, p = 0.007). The findings showed that STEM methods are highly effective in fostering soft skills such as communication, teamwork, problem-solving, and critical thinking. The results of this research confirm that the systematic integration of soft skills development into STEM education is a powerful strategy for ensuring the professional and social adaptation of future specialists.